(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
At the Drodesera Festival / Supercontinent 2017 was presented Lebanese artist Raafat Majzoub’s installation The Perfumed Garden / Hekmat, xx. Part of a larger project to write a serial novel that originated in 2012 and has not yet been completed, in this stage Majzoub participates in the installation by writing a new chapter of the novel from his residence in Beirut. Unlike other performances that saw the author present, Hekmat, xx / Dro is confronted with a particular performative strategy that discusses the degree of presence/ absence of the artist, reconfigured through the mimetic passage in the narrative form and distant intervention. By updating a document shared on the GDrive platform and displayed on the screen of a laptop open on a desk, the artist makes visible to the user the act of creating a piece of text while not being physically present. The group of users visits and interacts (listening, watching, acting) in a physical space and enters into a specific and complex relationship with the author. Examining the artist’s critical writings and comparing them with theoretical sources, the essay investigates Majzoub’s project by analyzing an experiment that employs different degrees of mediated performance to express a series of artistic, philosophical and political instances.